Efficient Market Hypothesis and Market Anomalies of LQ 45 Index in Indonesia Stock Exchange - Helma Malini (Faculty of Economics, Universitas Sriwijaya, 2019)
The validity of Efficient Market Hypothesis (EMH) needs to be examine and investigate throughout the time, particularly relates with the existence of Calendar Effect in one country stock exchange. LQ 45 Index is one of the Index that known as the most liquid index in Indonesia stock exchange, however the liquidity of this Index is influenced by many factors including past prices and calendar effect. This paper investigates the existence of EMH in Indonesia where the result showed that weak form EMH exist in LQ 45 Index. The result also showed that during certain condition investor are not able to gain profit in LQ45 Index using historical share prices data